Immigration, Integration and Citizenship in Portugal: The Case of Health Policy - Asensio, M.; Padilla, B. (Globalization,Territories and Integration, IASIA-LAGPA Conference, Lima (Peru), 23-26 July 2018, 2018)
The aim of this study is to analyze the use of healthcare services among migrants and to identify the main gaps in healthcare utilization between migrants in Portugal. As we will see, understanding recent immigration to Portugal and the legal frameworks set to manage these flows can illuminate not only the contradictions of Portuguese society but also the broader contradictions of the Welfare State in the new global economy. This analysis can make contributions at various levels. First, this research helps to understand the aforementioned paradoxes of a greater control of immigration in times of intense globalization. Second, we hope to contribute to developing the concepts that migration has brought to Portugal, not just in terms of involving cultural issues but also other dimensions that are systematically produced by law and the structural and economic imperatives it secured. Third, this case study adds to the ongoing discussion of the pathways to promote the integration of immigrants that lack access to documentation on their residence status according to the legal framework.